Household- Versus Incentive-Based Contact Investigation for Tuberculosis in Rural South Africa: A Cluster-Randomized Trial. (2nd December 2022) - Hanrahan, Colleen F; Nonyane, Bareng Aletta Sanny; Lebina, Limakatso; Mmolawa, Lesego; Siwelana, Tsundzukani; West, Nora S; Albaugh, Nicholas; Martinson, Neil; Dowdy, David W
Abstract: Background: Household contact investigation for people newly diagnosed with tuberculosis (TB) is poorly implemented, particularly in low- and middle-income countries. Conditional cash incentives may improve uptake. Methods: We conducted a pragmatic, cluster-randomized, crossover trial of 2 TB contact investigation approaches (household-based and incentive-based) in 28 public primary care clinics in South Africa. Each clinic used 1 approach for 18 months, followed by a 6-month washout period, after which the opposite approach was used. Fourteen clinics were randomized to each approach. In the household-based arm, we conducted TB screening and testing of contacts at the household. In the incentive-based arm, both index patients and ≤10 of their close contacts (either within or outside the household) were given small cash incentives for presenting to study clinics for TB screening. The primary outcome was the number of people with incident TB who were diagnosed and started on treatment at study clinics. Results: From July 2016 to January 2020, we randomized 28 clinics to each study arm, and enrolled 782 index TB patients and 1882 contacts in the household-based arm and 780 index patients and 1940 contacts in the incentive-based arm. A total of 1413 individuals started on TB treatment in the household-based arm and 1510 in the incentive-based arm. The adjusted incidence rate ratio of TB treatment initiation in the incentive- versus household-based arms was 1.05 (95% confidence interval: .97–1.13). Conclusions: Incentive-based contact investigation for TB has similar effectiveness to traditional household-based approaches and may be a viable alternative or complementary approach to household-based investigation. Abstract : The use of small cash incentives for tuberculosis contact investigation is feasible and acceptable in rural South Africa and has a yield similar to more costly household-based contact investigation.